The central shrine of the Triple-Shrine Temple - Temples of India Project Team (Jio Institute, 2024)
The central shrine of the Triple Shrine Temple is a later addition to the edifice. Built in red sandstone, this single-shrine temple is also adorned with a shikhara (superstructure) of the latina (mono-spire) variety. The base mouldings and the wall of this shrine are built in a pancharatha design, that is, consisting of five divisions to the plan and elevation. The finial of the shikhara has amalaka (ribbed disc). The temple exterior does not have any sculptures or ornamentation. The latina shikhara has small aedicules on the corners and a mulashringa (main spire) consisting of five bands. The corner bands of the shikhara have seven blocks separated by flat ribbed discs.